Possibility of Repeated Use of Elite Donor Cows for Mass Production of OPU-Derived Emb - Jong-In Jin; Byung-Hyun Choi; Seong-Su Kim; Bun-Young Park; Jung-Gyu Lee; Il-Keun Kong (The Korean Society of Animal Reproduction and Biotechnology, 2015)
This study was designed to know the possibility in repeat uses of elite donor cows for getting mass production of OPU-derived embryo production (OPU-IVP). Ultrasound transvaginal ovum pick-up (OPU) performed in 6 Korean native cows was aged 4 to 10 years old. The aspiration of immature oocytes for OPU derived embryo was carried out 2 times per week, and OPU-IVP of 1st period was carried out 22~48 sessions from each donors. And the break time for OPU-IVP of 2nd period after 1st OPU from each donors were 2~25 months. The OPU-IVP of 2nd period each donors conducted total 15~65 times for 2~8 months by an ultrasonographic, was guided follicular aspiration system. The average numbers of collected oocytes, grade 1 + grade 2(G1+G2) oocytes and cleavage embryo from 1st period OPU-IVP were significantly differences between donors (p<0.05). Total collected oocytes of donor D were significantly higher compared with donors of A, B, C, E and F (average 17.0 per session vs. 11.2, 10.1, 8.5, 10.2 and 9.6; p<0.05) and also oocytes of G1+G2 were significantly higher compared with r A and D and subsequently to donors of B, C, E and F (average 7.9 and 8.5 per session vs. 5.0, 2.7, 6.0 and 1.6; p<0.05). Cleavage rate of donor D was significantly higher compared with donors of A, B, C, E and F (average 13.1 per session vs. 10.1, 9.1, 6.9, 8.9 and 6.7; p<0.05). The average numbers of OPU-IVP for 1st period was significantly higher from donors of B, D and E than those from donors of A, C and F (average 6.5, 7.1 and 6.5 per session vs. 3.5, 4.2 and 2.8; p<0.05). The possibility investigation of 2nd OPU-IVP was carried out after 2~25 months rest periods from 1st period OPU session. Total average numbers of collected oocytes, cleavages and blastocyst development rates were significantly higher from 1st period OPU compared with 2nd period one (p<0.05). The OPU-IVP efficiency by break for more embryo production from elite cow was analysis comparing without rest of donor A, under 6 months rest period as B and over 6 months rest period as C and then the average numbers of collected oocytes, cleavages and blastocysts were significantly higher from A group (11.8, 9.5 and 5.2 per session) than those from B and C groups (7.9, 6.2 and 2.6 vs. 9.2, 7.5 and 3.9, p<0.05), and also C group was significantly higher than B group. In conclusion, 1st period OPU-IVP was more efficient compared with 2nd period repeated uses of donor, and the break times for additional production of embryo on donor were needed more than over 6 months after 1st period OPU-IVP. This repeating uses of elite donor cows given more emphasis for getting the opportunity on mass production of elite cow OPU-IVP embryo should be increased G1+G2 possibility of genetic improvement of livestock within short period.